Freshwater hyphomycetes in Sordariomycetes: two new species of Tainosphaeria (Chaetosphaeriaceae, Chaetosphaeriales) from Thailand - Li, Chun-Xue; Yu, Xian-Dong; Dong, Wei; Hu, Dian-Ming; Boonmee, Saranyaphat; Zhang, Huang (Phytotaxa, 2021)
Ongoing investigation of diversity and taxonomy of lignicolous freshwater fungi in Thailand have revealed plenty of new hyphomycetous species. In this study, Tainosphaeria aquatica sp. nov. and T. thailandense sp. nov., occurred on submerged wood in Thailand, are described and illustrated based on the evidences of morphological characters and phylogenetic analysis of combined LSU, ITS and TEF1-α dataset. Tainosphaeria aquatica is characterized by hyaline, 0–3-septate, cylindrical to long fusiform conidia with hair-like, hyaline appendages at both ends. Tainosphaeria thailandense is distinct in having laurel-green, 0–1-septate, reniform to ellipsoidal conidia with polar appendages. A synopsis of morphological characteristics of Tainosphaeria species is provided.